Schistosoma mansoni: immunodepression of hepatic schistosome granuloma formation in mice infected by Trypanosoma cruzi - O. Genaro; Z. Brener; P.M.Z. Coelho (Revista da Sociedade Brasileira de Medicina Tropical, 1986)
Infection by Trypanosoma cruzi in mice depresses hepatic granuloma formation around Schistosoma mansoni eggs. This immunodepressive effect occurred in mice with Chagas' disease at the acute and/or chronic phases, granulomas being signijicantly smaller than those in Controls. Data suggest that Chagas ' disease depresses the delayed hypersensitivity immune response directly.